Biotransfer of Cd along a soil-plant- mealybug-ladybird food chain: A comparison with host plants. (February 2017) - Wang, Xingmin; Zhang, Can; Qiu, Baoli; Ashraf, Umair; Azad, Rashid; Wu, Jianhui; Ali, Shaukat
Abstract: Agro-ecosystem contamination by the heavy metals present in different agricultural products is a serious challenge faced by the living organisms. This study explains the cadmium (Cd) transfer from soils contaminated with different cadmium concentrations through a plant (eggplant and tomato) - mealybug ( Dysmicoccus neobrevipes) - predator ( Cryptolaemus-montrouzieri) food chain. The soils were amended with Cd at the rates of 0, 12.5, 25 and 50 mg/kg (w/w). Our findings showed that considerably higher Cd transfer through tomato plant. Cadmium was biomagnified during soil-root transfer while bio-minimization of Cd was observed for shoot-mealybug – ladybird transfer. Our results further showed sequestration of Cd during the metamorphosis of ladybird beetle whilst transfer of Cd through soil-plant-mealybug-ladybird multi-trophic food chain increased in a dose dependent manner. Our results emphasize the need of further studies to elaborate possible mechanisms of Cd bio-minimization by plants, mealybugs and ladybirds observed during this study. Graphical abstract: Highlights: This study explains the transfer of Cd through a food chain consisting of plants (eggplant and tomato), pink hibiscus mealybug ( Dysmicoccus neobrevipes) and its predator ( Cryptolaemus montrouzieri). The Cd transfer was effectively reduced in shoot-mealybug – ladybird food chain. The Cd body burdens in C. montrouzieri adults were lower than mealybugs showing a considerable bio-minimization of Cd. The percentage of Cd body burden lost in pupal exuviae decreased with increase in body burden of adults. Tomato plants were more tolerant to the Cd amendments when compared to eggplants.